Mapping ion-induced mesophasic transformation in lyotropic in situ gelling system and its correlation with pharmaceutical performance - Patil, Sharvil S.; Venugopal, Edakkal; Bhat, Suresh K.; Mahadik, Kakasaheb R.; Paradkar, Anant R. (Pharmaceutical Research, 2013)
To investigate influence of ion induced mesophasic transformation on pharmaceutical performance of in situ gelling system consisting of glyceryl monooleate. The prepared system showed mesophasic transformation during its conversion from sol to gel upon controlled hydration. The process of mesophasic transformation was studied by SAXS, DSC, rheology and plane polarized light microscopy. Further the influence of additives i.e. naproxen salts (sodium and potassium) and naproxen (base) on the process of mesophasic transformation was also elucidated. It was observed that addition of salt form of naproxen transformed W/O emulsions into cubic mesophase whereas addition of base form of naproxen formed reverse hexagonal (H-II) phase upon controlled hydration. The cubic mesophase formed by naproxen salts retarded the drug release for initial 3 h whereas H-II phase showed sustained drug release characteristics for naproxen base following Higuchi drug release kinetics. The current work suggests that formulations with tailor made pharmaceutical performance can be developed by selecting proper additives in the system so as to obtain the desired mesophase `on demand' thereby controlling drug release characteristics.
Keywords: cubic phase; hexagonal phase; liquid crystal; mesophasic transformation; sustained drug release